Imbalanced Innate Lymphoid Cells are Associated With Disease Activity and Arthritis Involvement in Patients With Systemic Lupus Erythematosus - Yanni JIANG; Yi ZHAO; Yi LIU; Qiaorong HUANG; Wentong MENG; Hong XU; Xianming MO (Archives of Rheumatology, 2020)
Objectives: This study aims to evaluate the frequency and absolute number of circulating innate lymphoid cell (ILC) subsets and their associations with clinical and serological features in systemic lupus erythematosus (SLE). Patients and methods: We recruited 28 SLE patients (6 males, 22 females; mean age 37.57 years; range, 18 to 56 years) and 13 healthy controls (4 males, 9 females; mean age 32.08 years; range, 19 to 48 years). Circulating ILC subsets were identified by flow cytometry. Associations between all detected cells and SLE disease activity, clinical manifestations, and serum autoantibodies were analyzed. Results: In this study, significantly higher frequencies of ILC2s and ILC3s, lower frequencies of ILC1s, and higher ILC1/ILC3 and ILC1/ILC2 ratios were observed in SLE patients than in healthy controls. The frequencies and number of ILC3s were positively associated with SLE disease activity index 2000 score and anti-double stranded deoxyribonucleic acid titers in patients with SLE. Decreased ILC1 frequencies, increased ILC3 frequencies, and decreased ILC1/ILC3 and ILC2/ILC3 ratios were observed in patients with arthritis compared to those without arthritis. Conclusion: Our results indicated biased altered distributions of circulating ILC subsets in SLE. ILC3s were associated with SLE disease activity, and ILC1s, ILC3s, and ILC1/ILC3 and ILC2/ILC3 ratios were associated with SLE accompanied with arthritis. Taken together, these results suggest that ILCs may serve as cellular biomarkers for disease activity and arthritis involvement in SLE.